Pengaruh variable Marketing Mix terhadap Customer Loyalty Honda-Ramayana Basuki Rachmad Surabaya dengan Customer Satisfaction sebagai variable intervening - andrian wijoyo (Jurnal Strategi Pemasaran, 2014)
The purpose of this study was to determine: (1) Effect of Customer Satisfaction on Marketing Mix dealer Honda-Ramayana in Surabaya. (2) Effect customer satisfaction on Customer Loyalty Honda-Ramayana in Surabaya. (3) How big is the influence variables Marketing mix on Customer Satisfaction dealer Honda-Ramayana in Surabaya. The analysis implements in this research is causal analysis. This research is taken 120 consumers while data is collected by using questionnaire. Analysis technique use Partial Least Square (PLS).